Galeria z Wierzchowni. Preliminaria - Zieliński, Jan (Colloquia Litteraria, 2014)
Galer from Wierzchownia. Preliminaries The papter contains the analyis of Marcel Proust’s pastiche Sainte Beuve et Balzac, it juxtaposes the fragments from Balzac’s letters written by Proust with the original texts. The paper concentrates on the issues which are very rarely undertaen—Proust’s and Balzac’s attitudes to Poland before its partitions at the end of the 18-th century and its cultural heritage.